HLA-A, -B, -C, -DRB1, -DQB1, and -DPB1 Allele and Haplotype Frequencies of 28,927 Saudi Stem Cell Donors Typed by Next-Generation Sequencing - Jawdat, Dunia; Uyar, F. Aytül; Alaskar, Ahmed; Müller, Carlheinz R.; Hajeer, Ali (Frontiers in Immunology, 2020)
Human leukocyte antigen (HLA) allele and haplotype frequency distribution varies widely between different ethnicities and geographical areas. Matching for HLA alleles is essential for successful related and unrelated stem cell transplantation. Among the Saudi population, data on HLA alleles and haplotypes are limited. A cross-sectional study was performed on 28,927 bone marrow donors. The most frequent HLA alleles were HLA-A*02:01:01G (20.2%), A*24:02:01G (7.5%); B*51:01:01G (19.0%), B*50:01:01G (12.3%); C*06:02:01G (16.7%), C*07:02:01G (12.2%); DRB1*07:01:01 (15.7%), DRB1*03:01:01G (13.3%); DQB1*02:01:01G (29.9%), DQB1*03:02:01G (13.2%); and DPB1*04:01:01G (35.2%), DPB1*02:01:02G (21.8%). The most frequent HLA-A~C~B~DRB1~DQB1 haplotypes were A*02:01:01G~C*06:02:01G~B*50:01:01G~DRB1*07:01:01G~DQB1*02:01:01G (1.9%) and A*02:05:01G~C*06:02:01G~B*50:01:01G~DRB1*07:01:01G~DQB1*02:01:01G (1.6%). The most frequent HLA-A~C~B~DRB1~DQB1~DPB1 haplotypes were A*02:01:01G~C*15:02:01G~B*51:01:01G~DRB1*04:02~DQB1*03:02:01G~DPB1*04:01:0G (1%) and A*02:01:01G~C*07:02:01G~B*07:02:01G~DRB1*15:01:01G~DQB1*06:02:01G~ DPB1*04:01:01G (0.9%). Based on these haplotype frequencies, we provide forecasts for the fraction of patients with full matching and single mismatched donors for 3 to 6 loci depending on the registry size. With one million donors, about 50% of the patients would find an 8/8 match and 90% a 7/8 match. These data are essential for registry planning, finding unrelated stem cell donors, population genetic studies, and HLA disease associations.